Inhibition of lipopolysaccharide-induced suppression of luteal function in isolated perfused bovine ovaries - Elena STORNI; Heinrich BOLLWEIN; Anna-Katharina HANKELE; Olga WELLNITZ; Rupert M. BRUCKMAIER; Susanne E. ULBRICH; Johannes LÜTTGENAU (The Society for Reproduction and Development, 2021)
Recently, we observed that lipopolysaccharide (LPS) suppresses corpus luteum (CL) function in isolated perfused ovaries. It remained unclear if this suppression was due to increased luteal PGF2α secretion or LPS-induced apoptosis. Therefore, possible impacts of PGF2α and LPS were inhibited by a non-steroidal anti-inflammatory drug (flunixin) and an endotoxin-binding agent (polymyxin B), respectively. Bovine ovaries with a mid-cycle CL were collected immediately after slaughter and perfused for 240 min. After 50 min of equilibration, either flunixin or polymyxin B (5 μg/ml of each) were added to the perfusion medium of six ovaries, respectively. All ovaries (n = 12) were treated with E. coli LPS (0.5 μg/ml) 60 min after the onset of perfusion, and received 500 I.U. of hCG after 210 min of perfusion. Progesterone and PGF2α were measured in the effluent perfusate every 10 and 30 min, respectively. Biopsies of the CL were collected every 60 min to determine the mRNA expression of the cytokine TNFA and factors of apoptosis (CASP3, -8). Flunixin-treatment inhibited the increase of PGF2α after LPS-challenge that was observed in the polymyxin B-treated (PX-LPS) ovaries. After hCG-stimulation, progesterone secretion increased (P < 0.05) in group PX-LPS but not in the flunixin-treated (F-LPS) ovaries. Compared to initial values before LPS-challenge, luteal mRNA expression of TNFA and CASP3 was increased (P < 0.05) in group F-LPS at 120 and 180 min, respectively, and those of CASP8 was decreased (P < 0.05) in PX-LPS at 60 and 120 min after LPS-treatment. In conclusion, although flunixin managed to inhibit PGF2α, it did not suffice to successfully prevent LPS-induced apoptosis. However, endotoxin-binding polymyxin B resulted in luteal responsiveness to hCG after LPS-challenge.